A comparison of different densities of levobupivacaine solutions for unilateral spinal anaesthesia - Yagan,Özgür (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: The aim of the study was to compare the block characteristics and clinical effects of dextrose added to levobupivacaine solutions at different concentrations to provide unilateral spinal anaesthesia in lower extremity surgery. METHODS: This prospective, randomised, double-blind study comprised 75 ASA I-II risk patients for whom unilateral total knee arthroscopy was planned. The patients were assigned to three groups: in Group I, 60 mg dextrose was added to 7.5 mg of 0.5% levobupivacaine, in Group II, 80 mg and in Group III, 100 mg. Spinal anaesthesia was applied to the patient in the lateral decubitus position with the operated side below and the patient was kept in position for 10 min. RESULTS: The time for the sensorial block to achieve T12 level was slower in Group I than in Groups II and III (p < 0.05, p< 0.00). The time to full recovery of the sensorial block was 136 min in Group I, 154 min in Group II and 170 min in Group III. The differences were statistically significant (p < 0.05). The mean duration of the motor block was 88 min in Group I, 105 min in Group II, and 139 min in Group III and the differences were statistically significant (p < 0.05). The time to urination in Group I was statistically significantly shorter than in the other groups (p < 0.00). CONCLUSIONS: The results of the study showed that together with an increase in density, the sensory and motor block duration was lengthened. It can be concluded that 30 mg mL-1 concentration of dextrose added to 7.5 mg levobupivacaine is sufficient to provide unilateral spinal anaesthesia in day-case arthroscopic knee surgery.